2014
DOI: 10.3324/haematol.2014.104109
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of bortezomib, cyclophosphamide and dexamethasone in treatment-naive patients with high-risk cardiac AL amyloidosis (Mayo Clinic stage III)

Abstract: Bortezomib is an active agent in AL amyloidosis and responses to this drug in combination with cyclophosphamide and dexamethasone are both rapid and deep. Here we present an international, multicenter series of 60 patients with Mayo Clinic stage III cardiac amyloidosis to assess the impact of this regimen in improving outcomes in this poorrisk group. The median follow-up for the entire cohort is 11.8 months. The overall response rate was 68%. In a landmark analysis, examining patients who survived more than 3 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
70
3
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 114 publications
(80 citation statements)
references
References 26 publications
5
70
3
2
Order By: Relevance
“…In a broader view, the intrinsic toxicity for plasma cells of immunoglobulin fragments prone to misfolding and aggregation deserves to be explored in other monoclonal immunoglobulin-related diseases including light chain (AL) amyloidosis and LCDD, in which preliminary studies suggest that bortezomib-based therapy has a strong impact on renal and patient outcomes. 44,[60][61][62] Transgenic mouse models could be of invaluable interest to explore this issue. 36 Altogether, the present transgenic mouse model of HCDD accurately recapitulates the early steps of the human pathology and represents a valuable tool to explore the mechanisms that govern toxicity of truncated HCs and the sequential events leading to glomerular injury in MIDD.…”
Section: Discussionmentioning
confidence: 99%
“…In a broader view, the intrinsic toxicity for plasma cells of immunoglobulin fragments prone to misfolding and aggregation deserves to be explored in other monoclonal immunoglobulin-related diseases including light chain (AL) amyloidosis and LCDD, in which preliminary studies suggest that bortezomib-based therapy has a strong impact on renal and patient outcomes. 44,[60][61][62] Transgenic mouse models could be of invaluable interest to explore this issue. 36 Altogether, the present transgenic mouse model of HCDD accurately recapitulates the early steps of the human pathology and represents a valuable tool to explore the mechanisms that govern toxicity of truncated HCs and the sequential events leading to glomerular injury in MIDD.…”
Section: Discussionmentioning
confidence: 99%
“…Jeszcze całkiem niedawno amyloidoza serca wiązała się z bardzo złym rokowaniem, ponieważ mediana przeżycia od wystąpienia objawów HF wynosiła < 1 rok, ale postępy w leczeniu amyloidozy łańcuchów lekkich spowodowały poprawę rokowania [415].…”
Section: Amyloidoza Sercaunclassified
“…Chemotherapeutic regimens containing the proteasome inhibitor bortezomib have shown efficacy and good tolerance profile in both AL amyloidosis [26][27][28] and Randall-type MIDD [25] but their effect on the clearance of LC tissular deposits, although possibly accepted, remains to be demonstrated. Interestingly, Komatsuda et al [29] reported the disappearance of nodular mesangial lesions and disappearance of kappa light chain deposits in a patient with kidney LCDD under longterm chemotherapy.…”
Section: Discussionmentioning
confidence: 99%